Clarification of fibrin generation and degradation reaction processes of clot-fibrinolysis waveform in hemorrhagic disorders. - Tomoko Matsumoto; Nukumi Tujii; Daiki Shimomura; Aya Kouno; Takeshi Suzuki; Sho Shinohara; Nobuo Arai; Hiroshi Kurono; Osamu Kumano; Mikio Kamioka (PLoS ONE)
Clot-fibrinolysis waveform analysis (CFWA) is an assay used to simultaneously evaluate coagulation and fibrinolysis reactions. Although the assay detected the reaction via transmittance changes, there was no evidence that the transmittance changes indicated reactions. This study aimed to demonstrate that transmittance changes indicate coagulation and fibrinolysis reactions by detecting relative markers. CFWA was conducted using activated partial thromboplastin time (APTT) reagent and CaCl2 solution with tissue-plasminogen activator (tPA); transmittance changes were monitored, and the first derivative curve was analyzed in pooled normal plasma (PNP) and factors V, VIII, IX, X, and XI-deficient plasma samples. The samples during the coagulation and fibrinolysis reactions were prepared by adding the reaction stop solution, fibrin monomer complex (FMC), fibrin/fibrinogen degradation products (FDP), D-dimer and plasmin-α2 plasmin inhibitor complex (PAP) were measured to compare the waveform with the tendencies of these markers. The fibrinolysis markers FDP, D-dimer, and PAP increased in all samples as the reaction time increased. In FMC, the value increased during the coagulation phase, decreased at the end of the phase, and increased again during the fibrinolysis phase. FMC, FDP, and D-dimers were generated from fibrin/fibrinogen in the CFWA assay, indicating that the assay reflects coagulation and fibrinolysis reactions by monitoring transmittance.